Kinerja Isolator Kaca Bekas dan Berumur Terhadap Basic Insulation Level (BIL) - Naufal Hilmi Fauzan; Adhimas Daffa Kurnia; Prayudi Efendi; Prasetyohadi; Daryadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
High-voltage insulators are crucial for ensuring the reliability and safety of electrical systems operating under high voltage. Their primary function is to electrically separate phase conductors from each other and the ground. In designing electrical power systems, the basic insulation level (BIL) is a key parameter that must not be neglected, representing the maximum voltage the system can endure before a flashover occurs on the insulator. Besides voltage endurance, insulators are required to withstand environmental factors like temperature, humidity, and pollution, which can considerably affect their performance. This research examined the performance of glass insulators used at the Adipala power plant under diverse environmental conditions, comparing the outcomes against the BIL standard. Four testing scenarios were employed: optimal conditions, wet conditions, polluted conditions, and polluted insulators in humid environments. Findings indicate that wet conditions and the combined presence of pollution and humidity exert the most substantial impact on insulator performance. Under clean conditions with exposure to rain, insulator performance degraded by 19% to 25%. In contrast, when subjected to pollutants with an equivalent salt deposit density (ESDD) of 0.113816 mg/cm² and a non-soluble deposit density (NSDD) of 1.309962 mg/cm² at 90% humidity, performance diminished by 41% to 53%, falling significantly below the BIL threshold.